Alteration in ventral tegmental area and default mode network interplay and prediction of coma recovery in patients with sTBI. Issue 4 (April 2023) - Xu, Canxin; Zheng, RuiZhe; Zhou, LaiYang; Feng, DongFu
Abstract: Purpose: To investigate the role of VTA and DMN in modulating human consciousness in patient with sTBI. Methods: We mapped an atlas of VTA in the brainstem and a total of 19 region of interests in the ventral and dorsal DMN onto functional magnetic resonance imaging in 28 patients with sTBI and 28 healthy controls. We assessed the functional connectivity alteration in subcortical VTA and cortical DMN nodes in patients of coma. We evaluated the spatially distribution of FC alteration in VTA and DMN nodes after sTBI and evaluated their predictive value for coma recovery. Results: There was a decrease in FC between VTA and DMN in patients compared to controls. After decomposition, the FC between VTA and 10 DMN nodes were decreased whereas the FC within 2 DMN nodes were increased in patients with acute coma. The FC alteration in DMN nodes provided useful information for the early prediction of 6-month coma recovery in patients with sTBI. Conclusions: We provide initial evidence for the decreased FC between VTA and massive DMN nodes in patients with coma in acute phase of sTBI. We found that the FC alteration within DMN is more useful than the FC alteration between VTA and DMN for predicting coma recovery in patients with sTBI. VTA and DMN connectivity mapping provides an opportunity to advance the cortical-subcortical mechanism of human consciousness.